A method for preparing wear-resistant and heat-insulating fluororubber products

By using PTFE emulsion and glass fiber cloth impregnated with ceramic beads in fluororubber products, a composite structure is formed, which solves the shortcomings of existing fluororubber products in terms of wear resistance and heat insulation, and significantly improves their wear resistance and Thermal insulation performance extends the service life.

CN117801443BActive Publication Date: 2025-01-24WUXI HAOLITE SEALING TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311669494.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-01-24
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

Existing fluoroelastic products have shortcomings in wear resistance and heat insulation, especially under high temperature and high wear conditions, which can easily lead to seal failure.

Method used

Polytesylinylin emulsion with ceramic micro -beads on the glass fiber cloth layer, and add glass fiber cloth and ceramic micro beads to the outer layer or middle layer of fluorine rubber products to form a composite structure to improve wear -resistant resistance And insulation performance.

Benefits of technology

It significantly improves the wear resistance and heat insulation properties of fluororubber products, extends their service life, and avoids seal failure problems caused by wear and heat generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117801443B_ABST
    Figure CN117801443B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy, and discloses a fluororubber product, which is made of the following raw material components in parts by weight: 100 parts of fluororubber raw rubber; 5-20 parts of polytetrafluoroethylene emulsion; 10 parts of glass fiber cloth; 1-4 parts of vulcanizing agent; 15-35 parts of calcium silicon carbonate; 1-5 parts of magnesium oxide; 1-4 parts of calcium hydroxide; 2-5 parts of release agent; and 5-10 parts of ceramic microbeads. In the invention, a wear-resistant and heat-insulating impregnated glass fiber cloth layer is adhered to the outer layer of the fluororubber rubber, and the glass fiber cloth and the ceramic microbeads greatly increase the wear resistance of polytetrafluoroethylene, increase the hardness, and can better protect the fluororubber from damage caused by wear and heat generation, resulting in sealing failure, thereby greatly improving the service life of the fluororubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy technology, and more specifically, to a method for preparing wear-resistant and heat-insulating fluororubber products. Background Technology

[0002] Fluororubber products are generally chosen as sealing materials for new energy batteries. Fluororubber and polytetrafluoroethylene (PTFE) are often used in special working conditions due to their temperature resistance and media resistance. However, neither of them provides thermal insulation. PTFE has poor resilience, and fluororubber has insufficient wear resistance. It is possible to consider structurally combining the two. However, since the surface of PTFE is non-stick, it is difficult to combine it with fluororubber through simple adhesive. If PTFE is too thin, it is also difficult to achieve wear resistance and thermal insulation. The sealing performance of fluororubber will weaken due to temperature rise. Summary of the Invention

[0003] To address the above problems, the present invention provides a fluororubber product, characterized in that it is made from the following raw material components in parts by weight:

[0004] 100 parts of fluororubber raw rubber; 5-20 parts of polytetrafluoroethylene emulsion; 10 parts of glass fiber cloth; 1-4 parts of vulcanizing agent; 15-35 parts of calcium silicate carbonate; 1-5 parts of magnesium oxide; 1-4 parts of calcium hydroxide; 2-5 parts of release agent; 5-10 parts of ceramic microspheres.

[0005] A polytetrafluoroethylene emulsion impregnated with the ceramic microbeads is placed on a glass fiber cloth layer, which is on the outer layer of fluororubber and is used on the side requiring wear resistance.

[0006] The fluororubber layer is located on the other side where sealing is required, or even in the middle when both sides require both heat insulation and wear resistance.

[0007] Preferably, the mass ratio of calcium hydroxide to magnesium oxide is 1:(1.3-2.5).

[0008] Preferably, the mass ratio of the polytetrafluoroethylene emulsion to the ceramic microspheres is 5:(1.6-2.2).

[0009] Preferably, the fluororubber raw rubber is a combination of any one or more of binary or ternary raw rubbers; the fluorine content (%) of the fluororubber raw rubber is 60-70 wt%, and ML(1+10)@121℃ is 30-70 MU.

[0010] Preferably, the magnesium oxide is high-activity magnesium oxide 150; the calcium hydroxide is calcium hydroxide NICC5000, with a Ca(OH)2 content ≥95%.

[0011] A method for preparing a wear-resistant and heat-insulating fluororubber product includes the following steps:

[0012] S1: Mix raw fluororubber, plasticizer, calcium silicate carbonate, magnesium oxide, and calcium hydroxide and add them to an internal mixer for plasticizing. The initial temperature of plasticizing is 60°C, and the plasticizing time is 5 to 10 minutes.

[0013] S2: After plasticizing, add vulcanizing agent and mix internally at a temperature of 80-95℃ to produce fluororubber products in the initial stage of mixing.

[0014] S3: Add ceramic microspheres to polytetrafluoroethylene emulsion, mix the two together, impregnate the mixed solution into glass fiber cloth, sinter the impregnated glass fiber cloth and perform surface corona treatment, combine it with fluororubber after treatment, put it into a mold, add a release agent to the mold to perform co-vulcanization, freeze trimming to make fluororubber products.

[0015] Preferably, the co-sulfurization conditions in step S3 are a sulfurization pressure of 8–16 MPa, a sulfurization temperature of 160–180 °C, and a time of 15–30 min.

[0016] In summary, the present invention includes at least one of the following beneficial technical effects: In the present invention, a wear-resistant and heat-insulating impregnated glass fiber cloth layer is adhered to the outer layer of the fluororubber. The glass fiber cloth and ceramic microspheres greatly increase the wear resistance and hardness of polytetrafluoroethylene, which can better protect the fluororubber from damage caused by wear and heat generation, thus preventing sealing failure and greatly improving the service life of the fluororubber. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the O-ring in the outer layer of the impregnated fiberglass cloth.

[0018] Figure 2 The diagram shows the sheet material, with 1 and 3 representing the impregnated fiberglass cloth and 2 representing the liquid fluororubber layer. Detailed Implementation

[0019] This invention discloses a fluororubber product, which is made from the following raw material components in parts by weight:

[0020] 100 parts of fluororubber raw rubber; 5-20 parts of polytetrafluoroethylene emulsion; 10 parts of glass fiber cloth; 1-4 parts of vulcanizing agent; 15-35 parts of calcium silicate carbonate; 1-5 parts of magnesium oxide; 1-4 parts of calcium hydroxide; 2-5 parts of release agent; 5-10 parts of ceramic microspheres.

[0021] A polytetrafluoroethylene emulsion impregnated with the ceramic microbeads is placed on a glass fiber cloth layer, which is on the outer layer of fluororubber and is used on the side requiring wear resistance.

[0022] The fluororubber layer is located on the other side where sealing is required, or even in the middle when both sides require both heat insulation and wear resistance.

[0023] Furthermore, the mass ratio of calcium hydroxide to magnesium oxide is 1:(1.3~2.5).

[0024] Furthermore, the mass ratio of the polytetrafluoroethylene emulsion to the ceramic microspheres is 5:(1.6-2.2).

[0025] Furthermore, the fluororubber raw rubber is any one or a combination of binary or ternary raw rubber; the fluorine content (%) of the fluororubber raw rubber is 60-70 wt%, and ML(1+10)@121℃ is 30-70 MU.

[0026] Furthermore, the magnesium oxide is high-activity magnesium oxide 150; the calcium hydroxide is calcium hydroxide NICC5000, with a Ca(OH)2 content ≥95%.

[0027] A method for preparing a wear-resistant and heat-insulating fluororubber product includes the following steps:

[0028] S1: Mix raw fluororubber, plasticizer, calcium silicate carbonate, magnesium oxide, and calcium hydroxide and add them to an internal mixer for plasticizing. The initial temperature of plasticizing is 60°C, and the plasticizing time is 5 to 10 minutes.

[0029] S2: After plasticizing, add vulcanizing agent and mix internally at a temperature of 80-95℃ to produce fluororubber products in the initial stage of mixing.

[0030] S3: Add ceramic microspheres to polytetrafluoroethylene emulsion, mix the two together, impregnate the mixed solution into glass fiber cloth, sinter the impregnated glass fiber cloth and perform surface corona treatment, combine it with fluororubber after treatment, put it into a mold, add a release agent to the mold to perform co-vulcanization, freeze trimming to make fluororubber products.

[0031] Furthermore, the co-sulfurization conditions in step S3 are a sulfurization pressure of 8–16 MPa, a sulfurization temperature of 160–180 °C, and a time of 15–30 min.

[0032] Example 1

[0033] A fluororubber product is made from the following raw material components in parts by weight:

[0034] 100 parts of fluororubber raw rubber; 5 parts of polytetrafluoroethylene emulsion; 1 part of glass fiber cloth; 1 part of vulcanizing agent; 15 parts of calcium silicate carbonate; 1 part of magnesium oxide; 1 part of calcium hydroxide; 2 parts of release agent; 5 parts of ceramic microspheres;

[0035] A method for preparing a wear-resistant and heat-insulating fluororubber product includes the following steps:

[0036] S1: Mix raw fluororubber, plasticizer, calcium silicate carbonate, magnesium oxide, and calcium hydroxide and add them to an internal mixer for plasticizing. The initial temperature of plasticizing is 60°C and the plasticizing time is 7 minutes.

[0037] S2: After plasticizing, add vulcanizing agent and mix internally at a temperature of 90°C to produce fluororubber products in the initial stage of mixing.

[0038] S3: Ceramic microspheres are added to polytetrafluoroethylene emulsion and the two are mixed. The mixed solution is then impregnated into glass fiber cloth. The impregnated glass fiber cloth is sintered and subjected to surface corona treatment. After treatment, it is combined with fluororubber and placed in a mold. A release agent is also added to the mold to perform co-vulcanization. The co-vulcanization pressure is 13MPa, the vulcanization temperature is 170℃, and the time is 20min. Finally, the edges are frozen and trimmed to produce fluororubber products.

[0039] Example 2

[0040] A fluororubber product is made from the following raw material components in parts by weight:

[0041] 100 parts of fluororubber raw rubber; 8 parts of polytetrafluoroethylene emulsion; 1 part of glass fiber cloth; 1 part of vulcanizing agent; 15 parts of calcium silicate carbonate; 1 part of magnesium oxide; 1 part of calcium hydroxide; 2 parts of release agent; 6 parts of ceramic microspheres;

[0042] A method for preparing a wear-resistant and heat-insulating fluororubber product includes the following steps:

[0043] S1: Mix raw fluororubber, plasticizer, calcium silicate carbonate, magnesium oxide, and calcium hydroxide and add them to an internal mixer for plasticizing. The initial temperature of plasticizing is 60°C and the plasticizing time is 7 minutes.

[0044] S2: After plasticizing, add vulcanizing agent and mix internally at a temperature of 90°C to produce fluororubber products in the initial stage of mixing.

[0045] S3: Ceramic microspheres are added to polytetrafluoroethylene emulsion and the two are mixed. The mixed solution is then impregnated into glass fiber cloth. The impregnated glass fiber cloth is sintered and subjected to surface corona treatment. After treatment, it is combined with fluororubber and placed in a mold. A release agent is also added to the mold to perform co-vulcanization. The co-vulcanization pressure is 13MPa, the vulcanization temperature is 170℃, and the time is 20min. Finally, the edges are frozen and trimmed to produce fluororubber products.

[0046] Example 3

[0047] A fluororubber product is made from the following raw material components in parts by weight:

[0048] 100 parts of fluororubber raw rubber; 11 parts of polytetrafluoroethylene emulsion; 1 part of glass fiber cloth; 1 part of vulcanizing agent; 15 parts of calcium silicate carbonate; 1 part of magnesium oxide; 1 part of calcium hydroxide; 2 parts of release agent; 7 parts of ceramic microspheres;

[0049] A method for preparing a wear-resistant and heat-insulating fluororubber product includes the following steps:

[0050] S1: Mix raw fluororubber, plasticizer, calcium silicate carbonate, magnesium oxide, and calcium hydroxide and add them to an internal mixer for plasticizing. The initial temperature of plasticizing is 60°C and the plasticizing time is 7 minutes.

[0051] S2: After plasticizing, add vulcanizing agent and mix internally at a temperature of 90°C to produce fluororubber products in the initial stage of mixing.

[0052] S3: Ceramic microspheres are added to polytetrafluoroethylene emulsion and the two are mixed. The mixed solution is then impregnated into glass fiber cloth. The impregnated glass fiber cloth is sintered and subjected to surface corona treatment. After treatment, it is combined with fluororubber and placed in a mold. A release agent is also added to the mold to perform co-vulcanization. The co-vulcanization pressure is 13MPa, the vulcanization temperature is 170℃, and the time is 20min. Finally, the edges are frozen and trimmed to produce fluororubber products.

[0053] Example 4

[0054] A fluororubber product is made from the following raw material components in parts by weight:

[0055] 100 parts of fluororubber raw rubber; 14 parts of polytetrafluoroethylene emulsion; 1 part of glass fiber cloth; 1 part of vulcanizing agent; 15 parts of calcium silicate carbonate; 1 part of magnesium oxide; 1 part of calcium hydroxide; 2 parts of release agent; 8 parts of ceramic microspheres;

[0056] A method for preparing a wear-resistant and heat-insulating fluororubber product includes the following steps:

[0057] S1: Mix raw fluororubber, plasticizer, calcium silicate carbonate, magnesium oxide, and calcium hydroxide and add them to an internal mixer for plasticizing. The initial temperature of plasticizing is 60°C and the plasticizing time is 7 minutes.

[0058] S2: After plasticizing, add vulcanizing agent and mix internally at a temperature of 90°C to produce fluororubber products in the initial stage of mixing.

[0059] S3: Ceramic microspheres are added to polytetrafluoroethylene emulsion and the two are mixed. The mixed solution is then impregnated into glass fiber cloth. The impregnated glass fiber cloth is sintered and subjected to surface corona treatment. After treatment, it is combined with fluororubber and placed in a mold. A release agent is also added to the mold to perform co-vulcanization. The co-vulcanization pressure is 13MPa, the vulcanization temperature is 170℃, and the time is 20min. Finally, the edges are frozen and trimmed to produce fluororubber products.

[0060] Comparative Example

[0061] A fluororubber product is made from the following raw material components in parts by weight:

[0062] 100 parts of fluororubber raw rubber; 5 parts of polytetrafluoroethylene emulsion; 1 part of vulcanizing agent; 15 parts of calcium silicate carbonate; 1 part of magnesium oxide; 1 part of calcium hydroxide; 2 parts of mold release agent;

[0063] A method for preparing a wear-resistant and heat-insulating fluororubber product includes the following steps:

[0064] S1: Mix raw fluororubber, plasticizer, calcium silicate carbonate, magnesium oxide, and calcium hydroxide and add them to an internal mixer for plasticizing. The initial temperature of plasticizing is 60°C and the plasticizing time is 7 minutes.

[0065] S2: After plasticizing, add vulcanizing agent and mix internally at a temperature of 90°C to produce fluororubber products in the initial stage of mixing.

[0066] S3: Add polytetrafluoroethylene emulsion, place it in a mold, and add a release agent to the mold to make it co-vulcanized. The co-vulcanization pressure is 13MPa, the vulcanization temperature is 170℃, and the time is 20min. Finally, freeze and trim the edges to make fluororubber products.

[0067] Table 1. Raw material composition and dosage of fluororubber in Examples 1-4 and Comparative Example 1;

[0068]

[0069] Table 2 shows the heat insulation and abrasion resistance values ​​of fluororubber obtained by testing with instruments and equipment in Examples 1-4 and Comparative Example 1.

[0070] Test Items Example 1 Example 2 Example 3 Example 4 Comparative Example coefficient of friction 0.23 0.25 0.24 0.28 0.46 Surface temperature 35 32 34 31.5 37.1

[0071] According to the comparative examples in the table, the wear-resistant and heat-insulating impregnated glass fiber cloth layer is adhered to the outer layer of the fluororubber. The glass fiber cloth and ceramic microspheres greatly increase the wear resistance and hardness of polytetrafluoroethylene, which can better protect the fluororubber from damage caused by wear and heat generation, thus preventing sealing failure and greatly improving the service life of the fluororubber.

[0072] The above are all preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape and principle of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A fluororubber product, characterized in that: It is made of the following raw material components by weight: 100 parts of fluororubber raw rubber; 5-20 parts of polytetrafluoroethylene emulsion; 10 parts of glass fiber cloth; 1-4 parts of vulcanizing agent; 15-35 parts of calcium silicate; 1-5 parts of magnesium oxide; 1-4 parts of calcium hydroxide; 2-5 parts of release agent; 5-10 parts of ceramic micro beads; Placing the polytetrafluoroethylene emulsion impregnated with the ceramic micro beads on a glass fiber cloth layer, wherein the glass fiber cloth layer is on the outer layer of the fluororubber and is used for the side that needs to be wear-resistant; The fluororubber layer is on the other side that needs to be sealed, and even when both sides need to be heat-insulated and wear-resistant, the fluororubber layer is in the middle; The mass ratio of calcium hydroxide to magnesium oxide is 1:(1.3-2.5); The mass ratio of the polytetrafluoroethylene emulsion to the ceramic microbeads is 5:(1.6-2.2); The fluororubber raw rubber is any one or a combination of binary or ternary raw rubbers; the fluorine content (%) of the fluororubber raw rubber is 60-70wt%, and the ML (1+10) @ 121°C is 30-70MU; The magnesium oxide is high-activity magnesium oxide 150; the calcium hydroxide is calcium hydroxide NICC5000, and the content of Ca(OH)2 is ≥95%; The glass fiber cloth and ceramic microbeads increase the wear resistance of polytetrafluoroethylene, increase the hardness, and protect the fluororubber from damage caused by wear and heat generation, which may lead to sealing failure.

2. The method for preparing a fluororubber product according to claim 1, characterized in that: The following steps are involved: S1: adding fluororubber raw rubber, plasticizer, calcium silicon carbonate, magnesium oxide and calcium hydroxide into an internal mixer for plasticizing, wherein the initial temperature of plasticizing is 60°C and the plasticizing time is 5 to 10 minutes; S2: After the plasticizing is completed, the vulcanizing agent is added for internal mixing at a temperature of 80-95°C to produce the initial fluororubber product; S3: Ceramic microbeads are added to polytetrafluoroethylene emulsion, the two are mixed, and the mixed solution is impregnated into glass fiber cloth. The impregnated glass fiber cloth is sintered and subjected to surface corona treatment. After treatment, it is combined with fluororubber and placed in a mold. A release agent is also added to the mold to make it co-vulcanized, freeze-trimmed, and made into a fluororubber product.

3. The method for preparing a fluororubber product according to claim 2, characterized in that: The vulcanization conditions of the co-vulcanization in step S3 are: vulcanization pressure 8-16 MPa, vulcanization temperature 160-180° C., and time 15-30 min.

Citation Information

Patent Citations

  • Preparation method of polytetrafluoroethylene glass fiber wear-resistance plate

    CN102700196A

  • Ceramic microbead and high polymer material composite solid wear-resistant material, preparation method and application

    CN104031291A

  • Abrasion-resistant high-temperature-resistant tear-resistant fluorine rubber and preparation method thereof

    CN106317713A